High-flow priapism in a 12-year-old boy: Role of super-selective embolization - Rajagopal, Sasikumar; Kamarulzaman, Mohd Nazli; Y, Maya; Z, Zaidi; Syed, Hassan; Abdullah, Mohd Shafie; AR, Mossadeq; MD, Mohd Ashraf; Gohar, RMN; Mahamood, Z (Universiti Sains Malaysia, 2008)
Priapism is caused by an imbalance between penile blood inflow and outflow. There are two types, low flow priapism due to venous occlusion and high flow priapism due to uncontrolled arterial flow to the veins. High flow priapism most frequently occurs as a result of penile trauma where the intercavernosal artery discruption causes an arteriocavernosal fistula. It is rarely encountered in the pediatric and pre-pubertal population. Clinically it manifests as a painless, prolonged erection after perineal trauma. Treatment has ranged from expectant management to open surgical exploration with vessel ligation. We report the successful treatment of high flow priapism in a 12 year old pre-pubertal boy with superselective embolisation